2016
DOI: 10.1002/14651858.cd010406.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids as adjunctive therapy in the treatment of influenza

Abstract: BackgroundSpecific treatments for influenza are limited to neuraminidase inhibitors and adamantanes. Corticosteroids show evidence of benefit in sepsis and related conditions, most likely due to their anti-inflammatory and immunomodulatory properties. Although commonly prescribed for severe influenza, there is uncertainty over their potential benefit or harm. ObjectivesTo systematically assess the effectiveness and potential adverse effects of corticosteroids as adjunctive therapy in the treatment of influenza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(84 citation statements)
references
References 86 publications
2
76
0
6
Order By: Relevance
“…Altogether, the results of our study strongly highlight the need to identify the serotype infecting the patient before administering standard treatment regimens, such as, e.g., the increasingly used corticosteroids (45,50,53). Following coinfection during the acute phase of IAV infection, the invasive strains T4 and 7F caused stronger proinflammatory responses than those caused by the 19F strain.…”
Section: Discussionmentioning
confidence: 72%
“…Altogether, the results of our study strongly highlight the need to identify the serotype infecting the patient before administering standard treatment regimens, such as, e.g., the increasingly used corticosteroids (45,50,53). Following coinfection during the acute phase of IAV infection, the invasive strains T4 and 7F caused stronger proinflammatory responses than those caused by the 19F strain.…”
Section: Discussionmentioning
confidence: 72%
“…Remark 1: A systematic review of observational studies of corticosteroids administered to patients with SARS reported no survival benefit and possible harms (avascular necrosis, psychosis, diabetes, and delayed viral clearance) (62). A systematic review of observational studies in influenza found a higher risk of mortality and secondary infections with corticosteroids; the evidence was judged as very low to low quality owing to confounding by indication (63). A subsequent study that addressed this limitation by adjusting for time-varying confounders found no effect on mortality (64).…”
Section: Do Not Routinely Give Systemic Corticosteroids For Treatmentmentioning
confidence: 99%
“…Immune modulation for control of lung inflammation may be of help. Salvage therapy with corticosteroids failed in almost all clinical trials 1719 . The results with mTOR inhibitors remain ambiguous.…”
Section: Introductionmentioning
confidence: 99%